EPISTEMOLOGY OF INTELLECTUAL SCIENTIFIC SEARCH SYSTEMS - V. M. Koleshko; A. V. Goulay; V. A. Goulay (Наука и техника)
The paper studies problems pertaining to development of intellectual scientific search systems from the point of view of epistemology as a science on knowledge, its functioning and development. The most important epistemological postulates are determined in the paper and these postulates serve as a basis for an analysis of intellectual technologies of creative search and knowledge formation. Using a systematic approach to study of intellectual technologies of the innovation search the paper considers division of knowledge system in its components – properties of an object to be investigated (separate knowledge clusters). The mentioned approach and adopted biophysical analogies in the investigation of the intellectual technology on knowledge formation have made it possible to identify one of the key epistemology problems in respect of intellectual systems that is an initial uncertainty of scientific search purpose. In this connection a structure of value-orientated knowledge search in the intellectual medium is determined in the paper. The paper also analyzes process pertaining to transformation of value orientation of scientific search into its purposeful development. A role of intellectual systems of scientific search concerning knowledge synthesis of various cognate practices is considered in the paper. The paper proposes a variant pertaining to creation of generalized information image of the studied phenomenon in the intellectual medium on the basis of frame models of knowledge systems from various cognate practices.